The Second Oncogenic Hit Determines the Cell Fate of ETV6-RUNX1 Positive Leukemia - Rodríguez-Hernández, Guillermo; Casado-García, Ana; Isidro-Hernández, Marta; Picard, Daniel; Raboso-Gallego, Javier; Alemán-Arteaga, Silvia; Orfao, Alberto; Blanco, Oscar; Riesco, Susana; Prieto-Matos, Pablo; García Criado, Francisco Javier; García Cenador, María Begoña; et al. (Frontiers in Cell and Developmental Biology, 2021)
ETV6-RUNX1 is almost exclusively associated with childhood B-cell acute lymphoblastic leukemia (B-ALL), but the consequences of ETV6-RUNX1 expression on cell lineage decisions during B-cell leukemogenesis are completely unknown. Clinically silent ETV6-RUNX1 preleukemic clones are frequently found in neonatal cord blood, but few carriers develop B-ALL as a result of secondary genetic alterations. The understanding of the mechanisms underlying the first transforming steps could greatly advance the development of non-toxic prophylactic interventions. Using genetic lineage tracing, we examined the capacity of ETV6-RUNX1 to instruct a malignant phenotype in the hematopoietic lineage by cell-specifc Cre-mediated activation of ETV6-RUNX1 from the endogenous Etv6 gene locus. Here we show that, while ETV6-RUNX1 has the propensity to trigger both T- and B-lymphoid malignancies, it is the second hit that determines tumor cell identity. To instigate leukemia, both oncogenic hits must place early in the development of hematopoietic/precursor cells, not in already committed B-cells. Depending on the nature of the second hit the resulting B-ALLs presented distinct entities that were clearly separable based on their gene expression profiles. Our findings give novel mechanistic insight into the early steps of ETV6-RUNX1+ B-ALL development and might have major implications for the development of ETV6-RUNX1+ B-ALL prevention strategies.